INVESTIGATION OF THE LASER POWER ATTENUATION IN OPTICAL FIBER - Ali Al - Saidi, Imad Al - Deen Hussein (International Journal of Research -GRANTHAALAYAH, 2022)
Attenuation characteristics of the power of the laser beam in the optical fiber of different lengths were investigated. Two continuous wave (CW) diode lasers of two different wavelengths, 532 nm, and 671 nm, in the visible spectral region, were used for the injection of the laser beam into the optical fiber. The output powers of both lasers can be varied over the range 0 - 50 mW. The attenuation coefficient (α) of the optical fiber was determined for the chosen wavelengths, 532 nm, and 671 nm. The attenuation coefficient (α) was measured as a function of the laser input power (Pin) and the optical fiber length. The obtained results show that the power attenuation of the laser beam is wavelength dependent. The power attenuation is significantly affected by changing the wavelength of the injected laser beam. It is observed that the increase in the laser input power (Pin) leads to an appreciable decrease in the attenuation of the laser power in the optical fiber.